Analysis on factors affecting nausea and vomiting severity suffered by patients in the early phase of hemodialysis therapy - Muhammad Rafi Fathurrohman; Sri Suparti (UM Purwokerto Press, 2020)
Nausea and vomiting should be further checked and prevented, because these conditions can be a cause or complication during hemodialysis patients. Electrolyte and water imbalance (dehydration) can be considered as the main complication of nausea and vomiting itself. The aim of this study was to determine the factors that influence the severity of nausea and vomiting in patients undergoing hemodialysis. This type of research is quantitative with analytic descriptive method, with an approach using a retrospective cohort research design. The sampling technique in this study was a total sampling technique with a total sample of 57 patients. The research instrument used questionnaires and observations, data analysis using the Chi Square test and simple logistic regression analysis. The location of the study was the hemodialysis therapy site at the Islamic Hospital in Purwokerto in January-February 2020. The results showed that most of the respondents with the severity of nausea and vomiting, the patient's diet was not balanced (61.4%), the excess fluid had edema (63.2%), the gender was male (59.6%), female (40.4%). %), age 18-65 (57.9%), duration of HD <12 months (64.9%) and 58 respondents> 12 months (35.1). The results of bivariate analysis using logistic regression, obtained p value of the patient's diet 0.009, excess fluid, age and sex 0.001 and the duration of HD 0.003. From this analysis, there are 5 factors that can cause the severity of nausea and vomiting, namely the patient's diet, excess fluidity, gender, age, and duration of HD.